KONDISI SOSIAL EKONOMI BURUH TAHU DI KECAMATAN LUBUK SIKAPING KABUPATEN PASAMAN - Ghania Okta Viona; Surtani Surtani (JURNAL BUANA, 2022)
This study aims to determine 1). The income level of workers knows, 2). Conditions for meeting the clothing needs of tofu workers, 3). Conditions for meeting the needs of tofu workers' boards, 4). The conditions for meeting food needs need to know, 5). Conditions for meeting the educational needs of tofu workers' families, 6). The conditions for meeting the health needs of the workers' families know. The type of research used is descriptive quantitative. Thepopulation of all tofu workers in Lubuk Sikaping District is 35 people, while the sample uses the saturated sampling technique. The data collection technique used a questionnaire. The data analysis technique used was descriptive with a percentage formula. The results of the data recap were processed using a weighting system. Research results 1). The income condition of the tofu worker is between Rp. 1,000,000 - Rp. 1,500,000 / month. The majority of side jobs are as agricultural laborers with an income of between Rp. 410,000 - Rp. 500,000 / month, the majority of dependents are 5 people, 2). The condition of meeting the clothing needs of tofu workers with an average score of 2.9 is in the medium category, is classified as a capable condition, 3). The condition of meeting the needs of tofu workers' boards with an average score of 3.3 is in the medium category, is classified as a capable condition, 4). The condition of meeting the food needs of tofu workers with an average score of 3.4 is in the medium category, is classified as a capable condition 5). The condition of fulfilling the educational needs of the family of workers knows the average score of 3.1 is in the moderate category, but there are still many who are categorized as quite capable, 6). The condition of meeting the health needs of the family of tofu workers with an average score of 2.5 is in the low category,classified is underprivileged conditions.